2019
DOI: 10.1016/j.brat.2019.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Attentional disengagement from emotional information predicts future depression via changes in ruminative brooding: A five-month longitudinal eye-tracking study

Abstract: Brooding is considered a maladaptive form of emotion regulation linking adverse events to increases in depressive symptoms. The "Impaired Disengagement Hypothesis" (Koster, De Lissnyder, Derakshan & De Raedt, 2011) proposes that attentional disengagement processes are a main mechanism involved in the emergence and maintenance of brooding responses. In this study we tested prospective predictions derived from this framework, relying on eye-tracking to assess direct processes of attentional disengagement from em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 50 publications
6
31
0
Order By: Relevance
“…In their experimental study, Morrison and O’Connor (2008) obtained results suggesting that negative attentional bias shows a trend toward interacting with rumination and stress in predicting dysphoria 3 weeks later. Very similar results were obtained in the longitudinal study by Sanchez-Lopez et al (2019), who examined how baseline negative attention bias and high habitual ruminative responses cooperate with the subsequent occurrence of perceived stress to predict depression. They found that depression increases across time, especially in the case of individuals who reported a higher degree of adverse events and who were characterized simultaneously by both longer times when disengaging attention from negative information and higher ruminative brooding levels at the baseline assessment.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…In their experimental study, Morrison and O’Connor (2008) obtained results suggesting that negative attentional bias shows a trend toward interacting with rumination and stress in predicting dysphoria 3 weeks later. Very similar results were obtained in the longitudinal study by Sanchez-Lopez et al (2019), who examined how baseline negative attention bias and high habitual ruminative responses cooperate with the subsequent occurrence of perceived stress to predict depression. They found that depression increases across time, especially in the case of individuals who reported a higher degree of adverse events and who were characterized simultaneously by both longer times when disengaging attention from negative information and higher ruminative brooding levels at the baseline assessment.…”
Section: Introductionsupporting
confidence: 70%
“…Taking into consideration the initial evidence (Morrison and O’Connor, 2008; Sanchez-Lopez et al, 2019) suggesting that the co-occurrence of negative cognitive biases and high habitual use of rumination in combination with high perceived stress may be a predictor of depression level, the following research question was also formulated:…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the reliability of the related results and conclusions regarding AB is greatly reduced due to the poor split-half reliability of the DPT in the present study. More fine-grained and reliable AB estimates, such as eye-tracking, event-related potentials and functional magnetic resonance imaging, can be used in future studies [13,[90][91][92][93].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an increasing number of studies show that the reliability of the DPT is poor, which means that the DPT may not be suitable for assessing AB [ 88 , 89 ]. Therefore, more fine-grained and reliable AB estimates such as eye-tracking, event-related potentials and functional magnetic resonance imaging, can be used in future studies [ 13 , 90 93 ]. Nonetheless, we tested whether participants exhibited AB towards threat significantly greater than 0, and the result, t (121) = 3.417, p < 0.001, means that there is a significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, dispositional tendencies to brood are associated with sustained visual attention on sad faces, which indirectly suggests attentional inflexibility (Owens and Gibb, 2017). Finally, using an eye tracking task that delineated attentional engagement from disengagement in response to emotional and neutral valenced facial pairs, greater habitual brooding was predictive of slower disengagement from negative faces, particularly when experiencing high levels of daily stress (Sanchez-Lopez et al, 2019). Thus, perseverative processing of depression-relevant stimuli (likely reflective of inflexible disengagement from negative affective elicitors) could be a key antecedent to brooding.…”
Section: Introductionmentioning
confidence: 99%